INTERFACIAL TRANSITION ZONE CHARACTERISTIC OF POLYMERIC CONCRETE - Nuruddin, F (UTP, 2009)
The compressive strength development and microstructure properties through polymerization process of alkaline solution and fly ash blended with MIRHA is described in this paper. Three curing regimes, which are hot gunny curing, ambient curing, and external humidity curing, were investigated to obtain the suitable curing regime for cast in situ provision. Fly ash was blended with MIRHA for 0%, 3%, 5%, and 7%. Compressive strength and microstructure results indicated an improvement in the strength development with external exposure curing compared to hot gunny curing and ambient curing.